Textual History of L.N. Tolstoy’s Short Story “Three Elders” - Marina A. Mozharova (Studia Litterarum)
The article is the first to examine the textual peculiarities of the manuscripts of Leo Tolstoy’s short story “Three Elders,” published in 1886 in two different editions. The study of the autograph, two copies and proofreading of the story allows to get the notion of all stages of the author’s work as well as creating the pattern of alterations which appeared due to both unintentional mistakes and deliberate interference in the text from copyist V.G. Chertkov, who edited a new publication of the short story “Three Elders” in magazine “Niva” (1886, no. 13). The author of the article compares the two first printed texts of “Three Elders” and proves the choice as the main source the text published by S.A. Tolstaya in the edition: Count L.N. Tolstoy’s Works. Part 12. Late Works. M., 1886. The short story “Three Elders” was included into vol. 13 of The Complete Works of L.N. Tolstoy in 100 vols.